Computational Study of 3, 4-Diphenyl-1, 2, 5-Thiadiazole 1-Oxide for Organic Photovoltaics. (16th December 2009) - Glossman-Mitnik, Daniel
Abstract : We make use of a model chemistry within Density Functional Theory (DFT) recently presented, which is called CHIH-DFT, to calculate the molecular structure of 3, 4-diphenyl-1, 2, 5-thiadiazole 1-oxide (TSO), as well to predict its infrared (IR), ultraviolet (UV-Vis) and fluorescence (Fluo) spectra, the dipole moment and polarizability, the free energy of solvation in different solvents as an indication of solubility, and the chemical reactivity parameters that arise from Conceptual DFT. The calculated values are compared with the available experimental data for this molecule as a means of validation of our proposed model chemistry.